El imaginario distópico-apocalíptico en el teatro español actual de mujeres: hacia una nueva sensibilidad ecológica - Kumor, Karolina (Moderna Språk, 2024)
The dystopian boom has been prominent in narrative and cinema over the past few decades. However, more recently, playwrights have also turned their attention to the genre, bringing the dystopian imagination to the stage. This paper examines three plays written by Spanish women playwrights that address the ecological crisis: La redención by Ana Merino, Lavinia by Gracia Morales, and the cycle of “plastic dystopias” by Isabel Delgado. Despite their formal differences, all of these plays are part of the dystopian trend, as they incorporate many elements typical of the genre. The primary analytical approach focuses on the ecological emergency from a posthuman and ecofeminist perspective. Within this framework, we explore as well how dystopias reveal the mechanisms of exclusion inherent in the capitalist system. Our analysis concludes that the dystopian code functions effectively in the field of theatre, leveraging its dramatic power to critique society and promote a heightened ecological awareness.